Review paperOptical radiation in modern medicine - Sowa, Paweł; Rutkowska-Talipska, Joanna; Rutkowski, Krzysztof; Kosztyła-Hojna, Bożena; Rutkowski, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Optical radiation extends between microwaves and X-rays of the electromagnetic radiation and includes ultraviolet (UV), visible light (VL) and infrared (IR) components. The dose of radiation that reaches the skin is influenced by the ozone layer, position of the Sun, latitude, altitude, cloud cover and ground reflections. The photobiological effects of UV, VL and IR bands depend on their wavelength, frequency and mechanism of action. They are modified by the thickness, structure, vasculature and pigmentation of skin’s stratum corneum, epidermis and dermis. Following absorption, IR affects the body mainly through transfer of thermal energy to tissues. Visible light and skin interact either thermally or photochemically, whereas UV acts mainly photochemically. Optical radiation in the form of sunlight therapy had been used already in ancient times. Nowadays IR, VL and UV are widely applied in the therapy of allergic, dermatological, cardiovascular, respiratory, rheumatic, neonatal, pediatric and psychiatric disorders.